PENGARUH KINERJA KEUANGAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Askiantari, Anisa Eka; Purwanto, Agus (Diponegoro Journal of Accounting, 2024)
This research aims to analyze and obtain empirical evidence on the influence of financial performance and corporate social responsibility disclosure on firm value in manufacturing companies listed on the Indonesia Stock Exchange with good corporate governance as moderating variable during the period 2019-2021. GCG is measured by the composition of management shares and the proportion of the board of independent commissioners.This study utilized secondary data with a population size of 193 manufacturing companies listed on the Indonesia Stock Exchange during the period of 2019-2021. The sampling method used in this research is purposive sampling, where the sample consist of 61 manufacturing companies based on researcher-defined criteria. The analysis method employed in this research is moderated regression analysis (MRA).The result of this study indicate that financial profitability has positive effect on firm value, financial leverage has a negative effect on firm value, and CSR has a positive effect on firm value. However, good corporate governance represent by the composition of management shares does not moderate the relationships between financial leverage and firm value, and CSR and firm value. Independent commissioners moderate the relationships between financial profitability and firm value, and CSR and firm value